Investigating the effects of formative assessment on EFL students’ achievement and motivation: a Self-Determination Theory perspective - Zhang, Han; Quan, Jiale; Zhang, Ning; Zhang, Lingyu (Frontiers in Psychology, 2025)
IntroductionThis quasi-experimental study investigated whether formative assessment enhances EFL students’ motivation and English achievement. Drawing on Self-Determination Theory, which highlights autonomy, competence and relatedness as core psychological needs, the study examined how formative assessment may satisfy these needs to improve learning motivation.MethodsEighty-nine middle school EFL students in China participated in an eight-week quasi-experimental intervention. One group received formative-assessment-based instruction, while the comparison group experienced conventional teaching. Data were collected through SDT-based motivation questionnaires and English achievement tests.ResultsFindings showed that formative assessment most strongly enhanced students’ sense of relatedness, potentially due to closer peer and teacher relationships and greater enjoyment of English learning. Improvements in autonomy and competence were present but less substantial. Regression analysis further demonstrated that autonomy was the strongest predictor of English achievement, indicating its key role in linking motivational resources to learning outcomes.DiscussionThe study highlights the differential effects of formative assessment on students’ psychological needs and underscores the importance of autonomy in academic achievement. Several limitations are acknowledged, including the small sample size, single-school setting, brief intervention period, and possible cultural or teacher-related influences, all of which may constrain generalisability. Future research should adopt longitudinal designs, recruit more diverse samples, and investigate how specific formative assessment strategies uniquely support autonomy, competence and relatedness.